Application of WeChat Platform in Midterm Clinical Follow-Up of Children Who Underwent Transthoracic Device Closure of VSD - Xie,Wen-Peng (2022)
Abstract Introduction: The purpose of this study was to investigate the feasibility and superiority of using the WeChat platform for midterm clinical follow-up of children who underwent transthoracic device closure for ventricular septal defects (VSDs). Methods: Ninety children with VSDs who underwent transthoracic device closure were divided into a WeChat follow-up group (WFU group) and an outpatient follow-up group (OFU group). The patients were followed up via WeChat or at an outpatient clinic three months and one year after discharge. The incidences of adverse events, associated complications, costs and time spent, loss to follow-up rate, medication adherence, and overall satisfaction were recorded. Results: There was no statistically significant difference in the incidence of adverse events or postoperative complications between the two groups. Also, the loss to follow-up rate was similar between them. Compared with the OFU group, there were significant statistical advantages in the WFU group regarding the total time and cost spent, medication adherence, and satisfaction. Conclusion: The use of the WeChat platform in midterm clinical follow-up of children who underwent transthoracic device closure for VSDs has the advantages of reducing financial and time burdens, facilitating high medication adherence, and leading to high satisfaction.